Theoretical times - Redhead, Steve, 1952- (Emerald Publishing Limited, 2017)
In Theoretical Times, Steve Redhead describes the post-crash economic, environmental, political and cultural condition we live in today. As the rise of the international right - Donald Trump, Brexit, Marine Le Pen - swarms the globe, a new global battle within the right is developing: the globalists and neo-liberals versus the economic nationalists and protectionists. What then are the prospects for a resurrected theoretical politics of the left? Theoretical Times considers the work of theorists such as Alain Badiou, Slavoj Žižek, Jean Baudrillard and Paul Virilio, in this innovative reinvention of theory and the politics of theory. After the global financial crash the world is being hollowed out and we find ourselves in what Žižek calls a desperate state of hopelessness, the new dark ages. Accelerated culture sees us digitally entertaining ourselves to death but leaves us exhausted and frightened waiting for World War Three. Theoretical Times offers new theoretical resources as a way out of the quicksand.